Human capital and internet literacy impact on economic growth in Indonesia - Widarni, Eny Lestari; Irawan, Cahya Budhi; Harnani, Sri; Rusminingsih, Diah; Alim, Muhammad Birrul (Journal of Management, Economics, and Industrial Organization, 2022)
This study investigates the development of human capital in Indonesia through investment in education and health by the Indonesian government on job participation and economic growth. Modeling "autoregressive vectors" used to understand the causal link between variables required 21 years, from 2000 to 2020. The World Bank and the Indonesian Central Statistics Agency provided secondary data for this study. We use the variables of education, health, internet literacy, work participation, and economic growth in Indonesia. We found that internet literacy has a significant effect on economic growth and also provides a significant boost to education and health. Where education and health are the main factors forming human capital that have an impact on the quality of human resources. Improving the quality of education from the education and health development process has an impact on job participation. Employment participation itself encourages increased investment in education and health. This can illustrate the role of internet literacy and human capital on economic growth in Indonesia where economic growth can be boosted by increasing internet literacy and human capital.